Diagnosis, management and treatment of glucometabolic disorders emerging after kidney transplantation. (2nd May 2013) - Hornum, Mads; Lindahl, Jørn P.; von, Bengt; Jenssen, Trond; Feldt‐Rasmussen, Bo
Summary After successful solid organ transplantation, new‐onset diabetes (NODAT) is reported to develop in about 15–40% of the patients. The variation in incidence may partly depend on differences in the populations that have been studied and partly depend on the different definitions of NODAT that have been used. The diagnosis was often based on 'the use of insulin postoperatively', 'oral agents used', random glucose monitoring and a fasting glucose value between 7 and 13 mmol/l (126–234 mg/dl). Only few have used a 2‐h glucose tolerance test performed before transplantation. There is a huge variation in the literature regarding risk factors for developing NODAT. They can be divided into factors related to glucose metabolism or to patient demographics and the latter into modifiable and nonmodifiable. Screening for risk factors should start early and be re‐evaluated while being on the waitlist. Patients on the waiting list for renal transplantation and transplanted patients share many characteristics in having hyperglycaemia, disturbed insulin secretion and increased insulin resistance. We present guidelines for early risk factor assessment and a screening/treatment strategy for disturbed glucose metabolism, both before and after transplantation. The aim was to avoid the increased cardiovascular disease and mortality rates associated with NODAT.